Analysis of EFL Students’ Ability in Reading Vocabulary of Synonyms and Antonyms - Vina Fathira (Lectura : Jurnal Pendidikan, 2017)
Reading is an important thing for academic level. Every student must have manyvocabularies to encourage her/his reading skill. The aim of this research is to analyzethe students’ understanding of reading vocabularies of synonyms and antonyms in thehigher education level. Synonyms and antonyms are two important things should bemastered to get better reading comprehension. The method used in this research wasquantitative with survey design. The population same as the sample of this research wasfrom fifth semester students of STIBA Persada Bunda Pekanbaru. The procedures of theresearch were divided into 3 parts. First, students were asked to choose the best choicein the multiple choice for synonyms and anton, number and the wrong number, andgrouped the wrong number into difficulties level. Last, the researcher analyzed thestudents’ ability in reading vocabulary of synonyms and antonyms and concluded theresult of students’ ability in reading vocabulary of synonyms and antonyms inelementary, intermediate, and advanced level. The result of this research showed thatthe students’ ability in reading vocabulary of synonyms and antonyms was categorizedinto “excellent” level with mean score 85. From the three difficulties level of question,the findings of this research were explained every level of question. In synonyms, themean score of students’ ability were 89, 85, and 84 for elementary, intermediate, andadvanced level of question. Whereas, in antonyms, the mean score of students’ abilitywere 97, 85, and 69 for elementary, intermediate, and advanced level of question.